(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the development of computer software and applications, various types of recording media have emerged and evolved. This is a result of the rapid increase in the amount of data created by computers and the constant demand for large-capacity storage media. As large-capacity recording media have become available at low prices, the number of content production without being aware of the data capacity is increasing. Rather, content production often contains unnecessary features and effects for personal use. In this research, we will examine the feasibility of a practical system by carefully selecting the functions required for general use without excessive modification of effects. A floppy disk is used as the recording medium to limit the data size of the system.